Linking local and global economies : the ties that bind - Pietrobelli, Carlo, 1959-; Sverrisson, Árni (Routledge studies in the modern world economy, 2004)
This new book contains contributions on countries from Italy and Mexico to China and India. It recognises the disparity between conditions in these countries and poses interesting questions about post cluster globalisation.